Perilaku Perawat terhadap Penerapan Standar Operasional Prosedur Alat Pelindung Diri (Sop Apd) dalam Memberikan Pelayanan - Anda Syahputra; Marlina Marlina; Serlis Mawarni; Syahabuddin Syahabuddin (Malahayati Nursing Journal, 2023)
ABSTRACT Improving health status is not only aimed at the community but also for health workers who act as health service providers so that hospitals are obliged to make their workers healthy. Transmission of infection that occurs in nurses is caused because they work not wearing personal protective equipment. Nurse compliance in providing nursing care using PPE reflects the behavior of a professional nurse and can be influenced by individual factors, organizational factors, and psychological factors. To determine the effect of the behavior and characteristics of nurses on the application of standard operating procedures for personal protective equipment (PPE PPE) in providing services at the Cut Meutia General Hospital, North Aceh Regency in 2021. The type of research used in this research is Mixed Method research, namely Sequential Explanatory The sampling technique is proportional sampling with a sample of 40 people. Data analysis in this study uses unvariate, bivariate and multivariate analysis. From the characteristic variable, there is an influence of knowledge and attitude towards the application of PPE SOP, for education, length of work and training on the application of PPE SOP. There is an effect of nurse compliance on the application of PPE SOP. The results of the multivariate analysis found that nurses' attitude factors were very influential on the application of standard operating procedures for personal protective equipment (PPE) at the Cut Meutia General Hospital, North Aceh Regency in 2021 where the p value was found 0.05, the OR was 32.676 with 95% CI 3,046-350,504 negative attitude 32,676 times the possibility of not applying standard operating procedures for personal protective equipment (SOP PPE) compared to those who have a positive attitude. It can be concluded that there is an effect of nurse compliance on the application of standard operating procedures for personal protective equipment (SOP PPE) and the characteristics of attitudes that have the most influence on standard operating procedures for personal protective equipment (SOP PPE). Keywords: Nurse Compliance, Characteristics, PPE SOP  ABSTRAK Peningkatan derajat kesehatan bukan hanya ditujukan kepada masyarakat tetapi juga untuk tenaga kesehatan yang berperan sebagai pemberi pelayanan kesehatan sehingga rumah sakit berkewajiban menyehatkan para tenaga kerjanya. Penularan infeksi yang terjadi pada perawat disebabkan karena mereka bekerja tidak memakai alat pelindung diri. Kepatuhan  perawat dalam memberikan asuhan keperawatan dengan menggunakan APD mencerminkan perilaku dari seorang perawat profesional dan dapat dipengaruhi oleh faktor individu, faktor organisasi, dan faktor psikologis. Untuk mengetahui pengaruh perilaku perawat terhadap penerapan standar operasional prosedur alat pelindung diri (SOP APD) dalam memberikan pelayanan di Rumah Sakit Umum Cut Meutia Kabupaten Aceh Utara Tahun 2021. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian Mixed Method yaitu Sequential Explanatory Teknik pengambilan sampel secara proporsional  sampling dengan jumlah sampel 40 orang Analisa data dalam penelitian ini menggunakan analisa unvariat, bivariat dan multivariat. Dari variable karakteristi ada pengaruh kepatuhan, pengetahuan dan sikap terhadap penerapan SOP APD, untuk pendidikan, lama bekerja dan pelatihan tidak ada pengaruh terhadap penerapan SOP APD. Hasil analisa multivariat di dapati faktor sikap perawat yang sangat berpengaruh terhadap penerapan standar operasional prosedur alat pelindung diri (APD) di Rumah Sakit Umum Cut Meutia Kabupaten Aceh Utara Tahun 2021 dimana didapati nilai p0,05, diperoleh OR sebesar 32,676 dengan 95% CI 3,046-350,504sikap yang negative 32,676 kali kemungkinan tidak menerapan standar operasional prosedur alat pelindung diri (SOP APD) dibandingkan dengan yang memiliki sikap yang positif. Dapat disimpulkan ada pengaruh kepatuhan perawat terhadap penerapan standar operasional prosedur alat pelindung diri (APD) dan karakteristik sikap paling berpengaruh terhadap standar operasional prosedur alat pelindung diri (APD). Kata Kunci: Kepatuhan Perawat, Karakeristik, SOP APD